Effect of Walking Adaptability on an Uneven Surface by a Stepping Pattern on Walking Activity After Stroke - Sekiguchi, Yusuke; Honda, Keita; Izumi, Shin-Ichi (Frontiers in Human Neuroscience, 2022)
The purpose of the present study was to examine the relationship between walking adaptability on an uneven surface by step and walking activity in patients after stroke. We recruited 14 patients who had hemiparesis after stroke (age: 59.4 ± 8.9 years; post-onset duration: 70.7 ± 53.5 months) and 12 healthy controls (age: 59.5 ± 14.2 years) . For the uneven surface, the study used an artificial grass surface that was 7 m long with an approximately 2-cm leaf length. The subjects repeated even-surface and the uneven surface walking trials at least five times on a 7-m even walkway at a comfortable speed. We collected spatiotemporal and kinematic gait parameters on both the even and uneven surfaces using a three-dimensional motion analysis system. After we measured gait, the subjects wore an accelerometer around the waist at the height of the iliac crest on the right side in the healthy controls and on the non-paretic side in the poststroke patients for at least 4 days. We measured the number of steps per day using the accelerometer to evaluate walking activity. Differences in gait parameters between the even and uneven surfaces were calculated to determine how the subjects adapted to an uneven surface while walking. We examined the association between the difference in parameter measurements under the conditions of different surface properties and walking activity (number of steps per day) by using the Pearson product-moment and Spearman rank correlation coefficients. Walking activity significantly and positively correlated with the difference in paretic step length under the conditions of different surface properties in the poststroke patients (r = 0.65, p = 0.012) and step width in the healthy controls (r = 0.68, p = 0.015). The strategy of increasing the paretic step length, but not step width, on an uneven surface may lead to a larger base of support, which maintains stability during gait on an uneven surface in poststroke patients, resulting in increased walking activity. Therefore, in poststroke patients, an increase in paretic step length during gait on an uneven surface might be more essential for improving walking activity.